Protecting Student Privacy in Digital Education: A Systematic Review of Wearable Technology Policies in Southeast Asia - Iman Cahyanto; Manuel E. Caingcoy; Andy Sutrisno (Tarbawi: Jurnal Keilmuan Manajemen Pendidikan, 2025)
This paper seeks to review the current policies related to the application of wearable devices in education in Southeast Asia, focusing on privacy protection and compliance issues. A Systematic Literature Review (SLR) was performed according to PRISMA guidelines, considering the PICOS components. Relevant articles were searched in Scopus, Web of Science, IEEE Xplore, PubMed, and regional databases from 2015 to 2025. Results show significant differences in policy formulation and implementation among ASEAN member states, of which only 32% of the surveyed institutions have a full-fledged policy covering wearable technology. Significant challenges include divergent approaches to data protection, varying levels of institutional capacity, and limited awareness of privacy rights amongst privacy stakeholders. The study finds that the current frameworks must be better integrated to ensure that advancing technological innovation is balanced with solid privacy protection. These results have theoretical implications for educational digital rights and practical implications for policymakers, educators, and technology developers to promote ethical technology use and security.